2008
DOI: 10.1063/1.3035943
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic theory for particulate systems with bimodal and anisotropic velocity fluctuations

Abstract: Observations of bubbles rising near a wall under conditions of large Reynolds and small Weber numbers have indicated that the velocity component of the bubbles parallel to the wall is significantly reduced upon collision with a wall. To understand the effect of such bubble-wall collisions on the flow of bubbly liquids bounded by walls, a model is developed and examined in detail by numerical simulations and theory. The model is a system of bubbles in which the velocity of the bubbles parallel to the wall is si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…Fortunately, it has been shown that with known mean values ( εs, boldus, and u g ), it is possible to predict some of those structural parameters using the EMMS model, however, θ c and θ f cannot be predicted by currently available versions of EMMS model, therefore, one of our future targets is to include the fluctuation characteristics into the EMMS model so that θ c and θ f can be predicted as well. Note that (1) bimodal molecule/particle velocity distribution function for single phase, granular, or gas‐particle flow containing monodisperse gases or particles far from equilibrium is not new, but it is unclear what is the underlying mechanism of the bimodal distribution in previous studies. This study clearly shows that the bimodal distribution is due to the compromise of two different dominant mechanisms in competition, that is the physical principle of mesoscience; (2) Mei et al proposed to use a bimodal velocity distribution to represent the dilute‐dense flow structure in monodisperse gas‐fluidized beds, which is far beyond the equilibrium state.…”
Section: Emms‐based Particle Velocity Distribution Functionmentioning
confidence: 99%
“…Fortunately, it has been shown that with known mean values ( εs, boldus, and u g ), it is possible to predict some of those structural parameters using the EMMS model, however, θ c and θ f cannot be predicted by currently available versions of EMMS model, therefore, one of our future targets is to include the fluctuation characteristics into the EMMS model so that θ c and θ f can be predicted as well. Note that (1) bimodal molecule/particle velocity distribution function for single phase, granular, or gas‐particle flow containing monodisperse gases or particles far from equilibrium is not new, but it is unclear what is the underlying mechanism of the bimodal distribution in previous studies. This study clearly shows that the bimodal distribution is due to the compromise of two different dominant mechanisms in competition, that is the physical principle of mesoscience; (2) Mei et al proposed to use a bimodal velocity distribution to represent the dilute‐dense flow structure in monodisperse gas‐fluidized beds, which is far beyond the equilibrium state.…”
Section: Emms‐based Particle Velocity Distribution Functionmentioning
confidence: 99%
“…For hard-sphere collisions, the Boltzmann−Enskog collision term for fixed values of m and m * is given by ,,,, B ( m , m* , u ) = 1 π R 3 S + [ normalχ f false( 2 false) ( t , boldx , m , boldu ; boldx normalσ boldn , italicm* , boldu* ) f false( 2 false) ( t , boldx , m , boldu normal; boldx bold+ normalσ boldn bold, italicm* , boldu* ) ] false| g n false| d n d u* where the function f (2) denotes the pair distribution function, which can further be expressed (see Appendix A) in terms of the single-particle distribution function and a radial distribution function g 0 ( m ,ν, m *,ν*) depending on the solids volume fractions ν and ν*. [For example, for a binary system, an example expression for g 0 is g 0 …”
Section: Inelastic Boltzmann−enskog Kinetic Equationmentioning
confidence: 99%
“…Define first a velocity integral, corresponding to the source term for velocity moments due to inelastic hardsphere Boltzmann-Enskog collisions for given values of m and m* (see eq 2), by 3,4,11,21,35 (see Appendix A for more details)…”
Section: Derivation Of Moment Transport Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Francisco et al [48] presented a granular mixture model for elastic spheres subject to drag force with different mean velocities which cannot describe dissipation. Thus, the kinetic theory [49] of double granular temperatures and mean velocities makes sense not only for the binary granular mixtures but also for CFD simulation of fluidization [43,45,50,51].…”
Section: Introductionmentioning
confidence: 99%